2016
DOI: 10.1016/j.jnucmat.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of silver diffusivity in zirconium carbide to study the release behavior of 110mAg in the ZrC TRISO-coated nuclear fuel particle

Abstract: The tri-structural isotropic (TRISO) coated particle fuel has been developed and used for high temperature gas-cooled reactors (HTGRs). It provides a unique robustness of the first barrier for the fission products. The TRISO fuel particle has typically consisted of a UO 2 or UCO kernel, surrounded by successive layers of porous carbon, dense inner pyrocarbon, silicon carbide, and dense outer pyrocarbon. During operation, however, the SiC layer has been known to release radioactive silver 110m Ag which makes ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
1
11
0
2
Order By: Relevance
“…Due to neutron irradiation, Liang et al [24] found that (1) the buffer layer will experience cracks when the burn-up larger than 40,000 MWd/t; (2) PyC layer will undergo shrinkage to finally develop tensile stress, which can generate compression stress to the SiC layer; and (3) SiC layer will experience thermal decomposition at temperatures above 1600 0 C. Yang and Allen [25] conclude that SiC and PyC coating layers play an important role to provide a barrier to the release of gaseous fission product from the kernel. The integrity of the TRISO layers to retain gases and metallic fission products is still intact for temperatures of approximately 1600 0 C.…”
Section: Fuel Particle Coatingmentioning
confidence: 99%
“…Due to neutron irradiation, Liang et al [24] found that (1) the buffer layer will experience cracks when the burn-up larger than 40,000 MWd/t; (2) PyC layer will undergo shrinkage to finally develop tensile stress, which can generate compression stress to the SiC layer; and (3) SiC layer will experience thermal decomposition at temperatures above 1600 0 C. Yang and Allen [25] conclude that SiC and PyC coating layers play an important role to provide a barrier to the release of gaseous fission product from the kernel. The integrity of the TRISO layers to retain gases and metallic fission products is still intact for temperatures of approximately 1600 0 C.…”
Section: Fuel Particle Coatingmentioning
confidence: 99%
“…Data konduktifitas UN yang ditampilkan oleh Yang juga mirip dengan hasil yang diperoleh oleh Baranov. , 2016;Malkki, 2015).…”
Section: Analisis Sifat Termalunclassified
“…Akibatnya, integritas mekanik lapisan SiC akan berkurang, terutama setelah suhu mencapai 1700 o C karena akan terjadi transformasi dari b-SiC menjadi a-SiC serta mengakibatkan dekomposisi termal. Oleh karena itu penelitian mengganti SiC dengan ZrC saat ini sedang dilakukan dengan intensif (Yang, 2016;Porter dkk., 2013;Kim dkk., 2014). Senyawa ZrC berfungsi untuk penangkap oksigen yang akan membatasi pembentukan CO dan memperlambat migrasi kernel.…”
Section: Pelapisan Trisounclassified
“…The release of radioactive silver ( 110m Ag) in particular has been of considerable concern because it can contaminate various surfaces in the primary circuit of a direct-cycle HTGR and make maintenance difficult and thus costly [20,21]. However, there are few studies that address Ag retention in the ZrC TRISO-coated particle [22][23][24].…”
mentioning
confidence: 99%
“…For high temperature Ag diffusion experiments in ZrC, it has been difficult to find an effective experimental technique. To overcome such experimental difficulty in the present material system and make it possible to fabricate more reliable diffusion experimental samples, Yang et al [24] has recently developed a new experimental technique, referred to as the encapsulating source method. They fabricated a sample applying this method, diffusion annealed it, and determined the Ag diffusivity in ZrC at 1500 C with wavelength-dispersive X-ray spectroscopy (WDS).…”
mentioning
confidence: 99%